Perangkap Kemiskinan Kepala Rumah Tangga Perempuan di Kota Surabaya - Alie, Azizah; Elanda, Yelly; Wahyudi, Ruslan (Jurnal Community, 2024)
Poor women in urban areas are the most marginalized group because they occupy the second class economically and gender-wise. However, it turns out that poor women who are heads of families are the most vulnerable group and find it difficult to escape the poverty trap. The woman who is the head of the family in this study is a woman who is a widow. These poor women carry out a number of roles, namely as head of the household and housewife. This research aims to describe the experiences of poor women who are heads of households. This research will focus on the profile of poor female household heads in urban areas, the causes and shocks experienced by widowed women in facing poverty. The research method used is a feminist methodology. The results of the research show that there are three categories of poor women who have the status of heads of households in the city of Surabaya, namely female heads of households of productive age, potential elderly and non-potential elderly. Non-potential elderly female household heads and productive age female household heads as the sandwich generation are the families most vulnerable to falling into the poverty trap. The causes of poverty among female heads of households are poverty, isolation, helplessness, vulnerability and physical weakness. The shock experienced by female heads of households when they need education and medical expenses.